PENGARUH KOMPENSASI, EMPLOYEE ENGAGEMENT DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT PANORAMA JTB TOURS INDONESIA - Muhammad Daffa Alif Mufadhdhal, (2022)
This quantitative research was conducted to examine the effect of compensation, employee engagement and work motivation on employee performance. This research was conducted on employees of PT Panorama JTB Tours Indonesia. The method used is purposive sampling and the research sample obtained is 50 respondents. The data analysis technique used is the inferential test which uses the help of the PLS 3.0 program. The results of the partial and simultane testing obtained are that there is a positive and significant influence between compensation, employee engagement, work motivation on employee performance.